EDUCATION FOR PEOPLE OF THE “THIRD AGE” IN RUSSIA - A. N. Dzhurinskiy (Obrazovanie i Nauka)
Introduction. In today’s world, numbers of people of the senior generation are steadily increasing due to longer life expectancy. In this regard, questions of maintaining seniors’ working capacity, physical and psychological wellbeing and support of high vitality are updated. In this particular situation, an institute of formation of the “third age” is in high demand. The institution is considered as an integral part of a general continuous educational process during all life giving an opportunity to elderly citizens to stay actively full members of society.  The aim of the publication was to describe socio-pedagogical research and practical experience in the education of the elderly (the “third age”) in post-Soviet Russia at the turn of the 20th–21st centuries.Methodology and research methods. The research was based on socio-cultural approach to organisation of the education system, philosophical ideas about objective positivism, concept of continuous and non-formal life-long education and theory of comparative pedagogy.Results and scientific novelty. On the basis of scientific publications and documentary sources, many of which have until been out of the research field, the initial stage of genesis of education of the “third age” in Russia was systemically analysed. Its legislative base, tasks, contents of programmes and technology were investigated; the practicability of such education was esteemed. The representatives of the “third age” were characterised as members of education – in terms of their social activity, level of the previous educational preparation, cultural and educational inquiries and differentiation on gender. Desire for world outlook generalisation, mentorship and freedom from marginalization complex after retirement were noted. The practices of the first institutions and projects of education in the “third age” were analysed: retro clubs, open universities. The structure, curriculum and the results of the education of the “third age” were characterised by the example of “third age” universities in Orel, Stavropol and Chelyabinsk. Social, pedagogical, psychological and medical and recreational tasks of such educational organisations were designated; the humanistic principles and practice-focused orientations of their activity were emphasised. In addition, the shortcomings were listed: exaggerated encyclopedism of programmes, domination of verbal material presentation, unsuitable use of forms and methods for “aged” students; lack of the funded legal base of such education, its worthy financing and shortage of special teaching personnel. However, despite shortcomings and gaps, the social advantage of the education focused on satisfaction of essential needs and interests of elderly people is obvious. The results of monitoring outcomes and surveys, in particular, recorded a marked strengthening of physical and psychological health of students, emergence of vital incentives and decrease in intergenerational conflicts in their families. The similarities and distinctions of ideas and processes within the formation and development of the system of education of the “third age” in Russia and abroad were shown. The worldwide tendency of social turn towards the changed needs of elderly people was emphasised.Practical significance. The materials of the present research will make it possible to effectively cope with new challenges and solve current problems of additional education, which is oriented on a specific social stratum – older adults, taking into account their characteristics and expectations.